Some Remarks about the Muslim Population of the Empire in the Russian Government Handbook "Alphabetical List of the Population Living in the Russian Empire" - Feruza, Fayzieva (International Journal on Integrated Education, 2022)
The article aims at reviewing the national composition, number and occupation of the Muslim population of the Russian Empire on the basis of a historical document which is stored in the Turkestan Governor-General-General’s Department of the National Archive of Uzbekistan.